Development of a standardized approach for managing opioids in adults with chronic noncancer pain. (1st March 2018) - Downes, Jessica M.; Klepser, Donald G.; Foster, Jennifer; Nelson, Maggie
Abstract : Purpose: The implementation of a chronic pain protocol (CPP) and its effects on the management of long-term opioid therapy are described. Summary: The CPP used at a federally qualified health center and primary care clinic was updated in 2015 and included a prescribing ceiling in morphine equivalent dose (MED) per day and standardized the prescribing of chronic opioids. Intermittent urine drug screening performed at least once annually was added as a requirement of the pain management contract between the provider and the patient. An electronic report was developed to identify patients who were receiving long-term opioid therapy at the clinic. The clinical pharmacists identified patients from the report whose long-term opioid doses were over the clinic-recommended MED threshold, needed a pain contract, or were due for a urine drug screen. The number of patients for whom long-term opioids were prescribed decreased for all clinicians, including an 88% reduction by nurse practitioners. Over 12 months, 97 fewer patients with chronic pain were treated with a long-term opioid at the clinic. The number of patients with pain contracts increased by 22.9% ( p < 0.001), and the number of patients who had a urine drug screen over a 12-month period increased by 18.3% ( p = 0.0016). Conclusion: The implementation of a CPP and the development of electronic reports to track provider adherence to the protocol led to a reduction in the number of chronic pain patients receiving long-term opioid therapy. The number of patients with pain contracts increased.